Digital Integration In Tax Systems: Literature Review On Enhancing Efficiency And Ensuring Compliance - Kinanti, Kartika Ayu; Chandra, Yulian Ade; Suyono, Aji Prasetyo (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
Through a review of the literature, this study seeks to investigate how the digital transition affects tax compliance and efficiency. The application of technology like data analytics, e-filing, and e-payment is part of the digital transformation in tax administration. Based on a thorough analysis of multiple literature sources, it was discovered that these technologies greatly expedite administrative procedures, minimise human error, and improve data management and tax procedures' transparency. Because of the enhanced transparency, taxpayers are better able to comprehend their responsibilities, which encourages improved compliance. In summary, this study emphasises how crucial it is to implement digital technology in order to build a more effective, accountable, and transparent tax system, which will eventually increase tax compliance and collection.